2006
DOI: 10.1677/erc.1.01270
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to fulvestrant promotes overexpression of the c-Met receptor in breast cancer cells: implications for tumour–stroma interactions

Abstract: Our previous investigations using cell models of tamoxifen resistance have shown that the acquisition of an endocrine-insensitive state is accompanied by an invasive in vitro phenotype. In this study, we wished to determine whether this was specifically related to partial oestrogen receptor agonists or whether similar phenomena arise with the newer 'pure' anti-oestrogens, exemplified by fulvestrant. Our data demonstrate that the development of fulvestrant resistance in two breast cancer cell lines, MCF7 and T4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 45 publications
0
42
0
1
Order By: Relevance
“…Further models examined in log-phase comprised MCF-7-derived sub-lines that had acquired resistance to various endocrine strategies as follows: (1) the ER? MCF-7X model of acquired resistance to severe oestrogen deprivation (maintained in phenol-red RPMI medium supplemented with 5% heat-treated charcoal-stripped FCS [14] and (2) acquired anti-oestrogen resistant TAMR and FASR models (maintained in phenol-red-free RPMI medium containing 10 -7 M 4-OH-tamoxifen or Faslodex (FAS) [15][16][17]. All basal media were supplemented with penicillin-streptomycin (100 U/ml), fungizone (2.5 lg/ml), and L-glutamine (4 mM).…”
Section: Cell Culturementioning
confidence: 99%
“…Further models examined in log-phase comprised MCF-7-derived sub-lines that had acquired resistance to various endocrine strategies as follows: (1) the ER? MCF-7X model of acquired resistance to severe oestrogen deprivation (maintained in phenol-red RPMI medium supplemented with 5% heat-treated charcoal-stripped FCS [14] and (2) acquired anti-oestrogen resistant TAMR and FASR models (maintained in phenol-red-free RPMI medium containing 10 -7 M 4-OH-tamoxifen or Faslodex (FAS) [15][16][17]. All basal media were supplemented with penicillin-streptomycin (100 U/ml), fungizone (2.5 lg/ml), and L-glutamine (4 mM).…”
Section: Cell Culturementioning
confidence: 99%
“…We have previously demonstrated that the development of endocrine resistance in breast cancer cells is accompanied by an increased migratory capacity in vitro [19,29]. Given that FAK is a key regulator or such behaviour, we first determined whether the expression and/or activation status of FAK differed in endocrine-sensitive MCF7 cells versus two acquired endocrine-resistant MCF7 derivatives.…”
Section: Fak Is Diffe Rentially Activated In Endocrine-resistant Breamentioning
confidence: 99%
“…Since TamR and FasR cells display a highly migratory phenotype compared to their poorly-migratory MCF7 counterparts [19,29], we addressed the role of FAK in this process. Inhibition of FAK activity corresponded to a significant inhibition of both TamR and FasR cell migration over fibronectin ( Figure 4C).…”
Section: Inhibition Of Fak Activity Suppresses Cell-matrix Attachmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Os relatos da literatura demonstram casos de superexpressão do HGF em tumores mamários mais agressivos e resistentes ao tamoxifeno, corroborando com os nossos achados (Hiscox et al, 2006;Kuske et al, 2006). O Hif1a (fator indutor de hipóxia, subunidade1) é um fator de transcrição encontrado em células de mamíferos, nas quais o gene supressor tumoral VHL (Von Hippel-Lindau) provoca a ubiquitinação do Hif em resposta à mudança na oxigenação tecidual.…”
Section: Discussionunclassified